Paper joy for every room : 15 fun projects to add decorating charm to your home - Farion, Laure ([Schiffer Publishing], 2020)
What's the most fun way to add new creative touches to your living space? As followers of Laure Farion's brand PapierPapierPapier know, the answer is paper! Here are 15 stylish, joyful paper projects to decorate every room in the house. Take advantage of paper's inexpensive charms and Laure's lighthearted designs to make your spaces more stylish, more creative, and more colorful. With this book, your favorite papers, and a few basic household items like scissors and a ruler, you can add beautiful touches to the kitchen, the kids' rooms, adults' bedrooms, the office, and even the yard or balcony. Make a paper headboard for your bed and a sweet coin bank for the kids' room; create a cuckoo clock or an amazing paper houseplant. A tropical cabin nestled in a potted fern? Why not! Every craft lover will find that with these 15 basic patterns, and Laure's tips and tricks for getting the 3-D effects just the way you want them, the paper-crafting future is unlimited.